Gelatin-based Targeted Delivery Systems for Tissue Engineering - Zhai, Xinyue; Wu, Yuqian; Tan, Huaping (Current Drug Targets, 2023)
Gelatin is an attractive material for drug delivery and tissue engineering applications due to its excellent biocompatibility and biodegradability, which has been utilized as cell, drug, and gene carriers. Gelatin is less immunogenic compared to collagen and its precursor and retains informational signals, such as RGD (Arg-Gly-Asp) sequence, thus promoting cell adhesion and proliferation. To tune the mechanical strength and bioactivity, gelatin can be easily modified via chemical reactions and physical methods to obtain various derivatives. Furthermore, gelatin-based biomaterials can be achieved through chemical immobilization of specific molecules and physical combination with other biopolymers. This review focuses on the recent advances of gelatin and its derivatives as biomaterials in the field of drug delivery, including cell scaffolds for tissue engineering applications.
Keywords: regenerative medicine